Letter Archivement Information System in Department Earth Engineering Faculty of Engineering Universitas Syiah Kuala Based on Paperless Office - Bakar, Abu; Ismail; Albahri, Fauzan Putraga (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Incoming and outgoing mail information systems have an important role as a source of information and documentation media. As a source of information, archives are material/data for making the right decisions, so that archives can be said as a system that is interrelated with each other in a unified bond, because archives can support a program of organizational activities, both in terms of planning, implementation and controlling the tasks of the organization concerned, from leading activities to decision-making activities. Archives as documentation media, archives are official evidence that can be accounted for for government activities, therefore it is an obligation for every employee who works in the archives unit in this organization to carry out their duties properly, so that correspondence services can be more effective. and efficient, while the purpose of this study is to analyze the Archives Management System at the Department of Earth Sciences, Faculty of Engineering, Syiah Kuala University. In this study, researchers used descriptive research methods with a qualitative approach. This study aims to develop concepts and facts in depth to answer how the Archives Management System in the Department of Earth Sciences, Faculty of Engineering, Syiah Kuala University. The archive management system at the Department of Earth Sciences, Faculty of Engineering, Syiah Kuala University uses a number system and a dating system that is still less effective but has been running well, because it uses a combined procedure of centralization and decentralization. The Prototyping method is used as a software development model and evaluation activities are also carried out as an assessment of the results of the prototype built. Based on the evaluation of the appearance of the current desktop application. With the prototype design, it is known that each category has increased usability values. Content, Organization and Readability previously had a value of 0.64 and increased to 0.72. The Navigation category was previously 0.69 to 0.71. The previous User Interface Design category was 0.58 to 0.74 and the previous Performance and Effectiveness category was 0.62 to 0.72.